COASTAL POLLUTION IN ISTANBUL - BOZKURT KOPUZ, ESİN (My University, 2018)
Quantities of pouches filled with marine debris and packaging (kg) collected during coast andbeach cleaning, the amount of waste (m3) collected during sea surface cleaning and moss work (kg), andthe amount of sludge removed during stream rehabilitation (m3) were analyzed in Istanbul, Turkeybetween 2013 and 2016. Seasonal changes have been identified in these quantities. The quantity ofpackaging pouches collected during coastal cleaning had increased over time, reached its highest level in2016. High values were observed in September due to heavy rainfall and in the summer due to wastetransported from picnic areas. However, low values were seen for all parameters in winter. This increasein waste quantities can be eliminated by taking various precautions such as recycling or reusing plasticbags and bottles instead of throwing waste away. For a cleaner sea and coast, public education can bedeveloped to encourage these precautions. In addition, economic measures can be taken such as sellingplastic shopping bags instead of giving them free of charge.

İstanbul’da 2013 ve 2016 yılları arasında kıyı ve plaj temizliğinde toplanan deniz ve ambalaj atıklarının poşet sayısı, deniz yüzeyi temizliği ile toplanan atık miktarı (m³), yosun çalışması ile toplanan atık miktarı (kg) ve dere ıslahı ile çıkarılan çamur miktarı (m³) verileri analiz edilmiştir. Bu miktarlarda mevsimsel değişiklikler tespit edilmiştir. Kıyı temizliği sırasında toplanan ambalaj poşetlerinin miktarının zamanla aşırı yükseldiği ve 2016'da en yüksek seviyesine ulaştığı görülmüştür. Piknik alanlarından taşınan atıklardan dolayı yaz aylarında ve yoğun yağışla sürüklenmeden dolayı eylül ayında yüksek değerler gözlenmiştir. Ancak kış mevsiminde tüm parametreler için düşük değerler görüldü. Atık miktarlarındaki bu artış, atıkların atılması yerine plastik torbaların ve şişelerin geri dönüştürülmesi veya yeniden kullanılması gibi çeşitli önlemler alınarak giderilebilir. Daha temiz bir deniz ve sahil için, bu önlemleri teşvik etmek amacıyla kamu eğitimi geliştirilebilir. Ayrıca, plastik poşetler alışverişlerde ücretsiz verilmek yerine satılması gibi ekonomik tedbirler alınabilir.
İstanbul’da Kıyı Kirliliği
Keywords: Bilgisayar Bilimleri, Bilgi Sistemleri; Bilgisayar Bilimleri, Yazılım Mühendisliği; Mühendislik, Kimya; İnşaat Mühendisliği; Mühendislik, Elektrik ve Elektronik; Çevre Mühendisliği; Mühendislik, Jeoloji; Endüstri Mühendisliği; İmalat Mühendisliği; Mühendislik, Makine; Malzeme Bilimleri, Özellik ve Test; Metalürji Mühendisliği